2017
DOI: 10.1111/bjhp.12250
|View full text |Cite
|
Sign up to set email alerts
|

The journey between brain and gut: A systematic review of psychological mechanisms of treatment effect in irritable bowel syndrome

Abstract: A mediational model amalgamating the results of studies is proposed to illustrate the findings of the review. The model depicts the process by which psychotherapy changes illness-specific cognitions, behaviours, and anxiety to achieve reduction in symptom severity. Statement of contribution What is already known on this subject? Cognitive behavioural therapy (CBT) is the predominant psychological treatment for irritable bowel syndrome (IBS), although there is some research supporting other treatments such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 96 publications
2
51
0
1
Order By: Relevance
“…The finding that GI related cognitions and GI safety behaviours significantly mediated the treatment effect on both outcomes lends support to endogenous models of IBS. This fits with findings from previous mediation studies conducted in CBT trials for IBS, which have demonstrated the mechanistic roles of cognitions, behaviours and GI specific anxiety [16]. However, the finding that general anxiety was also a significant mediator provides some support for exogenous models of IBS.…”
Section: Mechanisms Of Treatmentsupporting
confidence: 89%
See 2 more Smart Citations
“…The finding that GI related cognitions and GI safety behaviours significantly mediated the treatment effect on both outcomes lends support to endogenous models of IBS. This fits with findings from previous mediation studies conducted in CBT trials for IBS, which have demonstrated the mechanistic roles of cognitions, behaviours and GI specific anxiety [16]. However, the finding that general anxiety was also a significant mediator provides some support for exogenous models of IBS.…”
Section: Mechanisms Of Treatmentsupporting
confidence: 89%
“…stress or general anxiety), are central maintaining factors of IBS [17]. While there is evidence to show that anxiety exogenous to IBS may have a causal role in the onset [19] and that those with IBS have increased stress reactivity [20,21], there is less evidence suggesting that changing such exogenous factors precede change in IBS symptoms [16]. A systematic review of treatment mechanisms in CBT for IBS suggested that across different CBT treatment protocols change in IBS-specific processes, particularly GI related cognitions, were key in reducing symptom severity and improving quality of life (QoL) [16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin also has significant anti-depressant and anti-anxiety behavior [ 34 ]. Due to the high prevalence of psychological comorbidities in patients with FAPDs [ 35 ], it was thought that curcuma species could be useful for the treatment of IBS. Although we did not find any data on the effect of turmeric in FAPDs in children, three studies in adults evaluated the effects of curcumin in patients with IBS [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, cognitive behavioral therapy was elucidated to be effective for patients with IBS. ( 40 ) 5-HT signaling is the reasonable target associated with GI symptoms and mental manifestation. Inhibition of TPH1 improved the symptoms in patients with IBS to a certain extent.…”
Section: Discussionmentioning
confidence: 99%